Application of Promotion, Map and Existing Tourism Information Systems in Solok Selatan District using Android Java Programming Language - Hari Marfalino; Larissa Rani; Mardison; Ichsan Pribadi (Universitas Putra Indonesia YPTK Padang, 2021)
The development of technology and information is felt very rapidly and this affects aspects of work that make work easier, one of which is the development of mobile technology, information media can now be made in the form of mobile applications, using mobile technology in the form of tourist applications, which provide information - information about tourism in the district of Solok Selatan, the search for tourism information in the district of Solok Selatan will be more practical to use and users can use this application wherever they are, this application can be used as a medium of knowledge about tourism in Solok Selatan district. This Solok Selatan tourist application is expected to be able to provide more knowledge about Solok Selatan tourism to the wider community, especially the people of Solok Selatan District.